Некласичннй класик. Твори Вітольда Ґомбровича в Україні - Нахлік, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The article is devoted to the problems of Witold Gombrowicz’s works reception in Ukraine. Conducting the research I not only collected translations of works by Gombrowicz in Ukraine and articles devoted to his personal life and creative work but also held an analysis of common and different features of his works reception in Poland and Ukraine.I tried to show the difference between European and post-socialistic literature canons.